Lutzomyia longipalpis urbanisation and control - Salomón, Oscar Daniel (2015)
Since the description of Lutzomyia longipalpis by Lutz and Neiva more than 100 years ago, much has been written in the scientific literature about this phlebotomine species. Soares and Turco (2003) and Lainson and Rangel (2005) have written extensive reviews focused on vector-host-parasite interactions and American visceral leishmaniasis ecology. However, during the last two decades, the success of Lu. longipalpis in colonising urban environments and its simultaneous geographical spreading have led to new theoretical and operational questions. Therefore, this review updates the general information about this species and notes the more challenging topics regarding the new scenario of urbanisation-spreading and its control in America. Here, we summarise the literature on these issues and the remaining unsolved questions, which pose recommendations for operational research.